Biofunctionalization of decellularized porcine aortic valve with OPG-loaded PCL nanoparticles for anti-calcification. Issue 21 (16th April 2019) - Li, Yang; Zhang, Yu; Ding, Jing-Li; Liu, Ji-Chun; Xu, Jian-Jun; Tang, Yan-Hua; Yi, Ying-Ping; Xu, Wei-Chang; Yu, Wen-Peng; Lu, Chao; Yang, Wei; Yang, Jue-Sheng; et al.
Abstract : A novel composite valve with controlled release OPG was prepared by introducing tissue engineering technology and nano drug-loading system to introduce anti-calcification biological factor OPG on the decellularized valve. Abstract : Decellularized valve stents are widely used in tissue-engineered heart valves because they maintain the morphological structure of natural valves, have good histocompatibility and low immunogenicity. However, the surface of the cell valve loses the original endothelial cell coverage, exposing collagen and causing calcification and decay of the valve in advance. In this study, poly ε-caprolactone (PCL) nanoparticles loaded with osteoprotegerin (OPG) were bridged to a decellularized valve using a nanoparticle drug delivery system and tissue engineering technology to construct a new anti-calcification composite valve with sustained release function. The PCL nanoparticles loaded with OPG were prepared via an emulsion solvent evaporation method, which had a particle size of 133 nm and zeta potential of −27.8 mV. Transmission electron microscopy demonstrated that the prepared nanoparticles were round in shape, regular in size, and uniformly distributed, with an encapsulation efficiency of 75%, slow release in vitro, no burst release, no cytotoxicity to BMSCs, and contained OPG nanoparticles in vitro . There was a delay in the differentiation of BMSCs into osteoblasts. The decellularized valve modified by nanoparticles remained intact and its collagen fibers were continuous. After 8 weeks of subcutaneous implantation in rats, the morphological structure of the valve was almost complete, and the composite valve showed anti-calcification ability to a certain extent.